Pelaksanaan Penghapusan Sertifikat Jaminan Fidusia Secara Elektronik Melalui Notaris di Kota Denpasar - Priyanto, I Made Dedy; Sawitri, Dewa Ayu Dian; Purwanti, Ni Putu (Acta Comitas : Jurnal Hukum Kenotariatan, 2024)
This study aims to determine the ability of debtors to delete fiduciary security certificates electronically through a Notary, as well as to determine the effectiveness of implementing electronic deletion of fiduciary security certificates through a Notary in Denpasar City. This research uses empirical legal research with a statutory approach and a factual approach. The results of this study explain that first, the debtor can delete the fiduciary certificate electronically through a notary after obtaining creditor approval. This must be proven by a statement in full and a request for deletion from the creditor. Second, the effectiveness of implementing the electronic deletion of fiduciary security certificates through a Notary in Denpasar City is not effective due to the lack of knowledge of Creditors and Debtors, registration of fiduciary security for the same object can be carried out without deleting it first, sanctions are not applied if they are late or do not do so. write-off, the write-off cost factor which is charged by the Creditor to the Debtor even though it is the Creditor's obligation, as well as the write-off interest factor which is with the owner of the object of the fiduciary guarantee/Debtor, but the Creditor as the recipient of the fiduciary guarantee must release the security right or carry out the write-off